Enhancing Community Energy Projects (CEPs) in Kenya: policy lessons from the United Kingdom (UK) - Kittony, Sharon; Onyango, Vincent; Duot, John Deng; Ologhadien, Nelson Goodnews; Pouhe, Stephanie Ngo (European Scientific Journal, ESJ, 2024)
This paper examines community energy projects (CEPs) in a developed (UK) and an emerging (Kenya) economy, focusing on renewable energy (RE) generation to address climate change and achieve universal energy access by 2030 (UN SDG Goal 7). While CEPs thrive in the UK, they are scarce in Kenya. Through comparative analysis examining CEPs historical trajectories, policy landscapes, and impacts on communities, the study aims to distil lessons that could inform Kenya’s CEPs development. Success in the UK suggests Kenya can replicate and adapt some CEPs models. By addressing existing challenges and adopting strategic policies and approaches, Kenya can unlock the full potential and impact of CEPs, contributing to sustainable energy transitions and achieving national development goals. Key lessons and recommendations include incentives like grant programs, feed-in-tariffs tariffs tailored for CEPs, adopting Smart Export Guarantee, implementing grid connection agreements, fostering collaborative task forces with community involvement, and centres for data and knowledge exchange.